PENGARUH PERPUTARAN KAS, PERPUTARAN PERSEDIAAN DAN PERPUTARAN PIUTANG TERHADAP PROFITABILITAS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2020-2022 - Latifah Eka Putri; Suprihati Suprihati; Muhammad Hasan Ma'ruf; Budiyono Budiyono (ITB AAS INDONESIA, 2024)
Profitability describes the company's ability to earn profits and effectiveness in managing company management. The level of profitability can affect the company's financial condition. This can be seen based on the ROA value. The type of research used is quantitative research. This research aims to determine the influence of cash turnover, inventory turnover and accounts receivable turnover on the profitability of manufacturing companies listed on the IDX in 2020-2022. The data collection method used purposive sampling and obtained 35 samples. The analysis model used was multiple regression analysis with SPSS data processing tools. The results of the test show that partially cash turnover has no significant effect on profitability, inventory turnover has no significant effect on profitability, and accounts receivable turnover has a significant effect on profitability.